Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Root accumulation and efficient translocation of steroids in mangrove plants: Implications for an overlooked coastal reservoir - Ji-Xun Chen; Nian-Nian Wu; Shan Liu; Yuan Liu; Qin-Ge Zhou; Qing-Song Yang; Juan Ling; Xiao-Fang Huang; Yan-Kuan Tian; Chang-Gui Pan; Xiang-Rong Xu (Marine Pollution Bulletin, 2026)

Regional assessment of multi-pool mangrove carbon across five coastal provinces of China: Heterogeneity, carbon accounting, and contextual screening - Yan Zheng; Wenhai Lu; Chang Liu; Hefeng Wang; Rong Zeng; Yan Xu; Yangyi Ai (Regional Studies in Marine Science, 2026)

DNA methylome analysis reveals EjABCG23-mediated epigenetic regulation underlying fruit russeting in white-fleshed loquat - Kun Zhang; Yuying Ding; Rong Su; Chang Liu; Xuelian Li; Yang Wang; Yan Deng; Qiong Zhou; Xiaojun Chen; Yuxing Li; Qunxian Deng (Postharvest Biology and Technology, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Construction and application of an antifouling transistor-based cytosensor for detection of CTCs - Rong Zou; Huiling Yan; Lei Wang; Yu Chen; Caiyuan Liao; Bowen Zhang; Gang Chang; Ping Wang; Hanping He (Chemical Engineering Journal, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Evaluating the effectiveness of marine ecological red lines: an integrated assessment of ecological outcomes and governance performance - Rong Zeng; Wenhai Lu; Chengliang He; Jie Liu; Yan Xu; Chang Liu; Yangyi Ai; Yan Zheng (Frontiers in Marine Science, 2026)
Marine protected areas worldwide often exhibit uneven conservation outcomes, largely due to differences in governance effectiveness and management implementation. As a large-scale spatial conservation policy, Marine Ecological Red Lines (MERLs) have been widely implemented in China to regulate human activities and safeguard critical marine ecosystems. However, their protection effectiveness remains insufficiently evaluated using quantitative and scalable approaches. In this study, we develop an indicator-based assessment framework grounded in the Pressure–State–Response (PSR) model to evaluate the effectiveness of MERLs. The framework integrates indicators of anthropogenic pressures, ecosystem conditions, and management responses, enabling spatially explicit and temporally comparable assessment. We apply this framework to MERLs in Hainan Province over a five-year period (2020–2024) and conduct systematic comparisons with adjacent non-protected areas. Furthermore, correlation analysis is used to examine the relationships between pressure reduction and ecological state changes, providing preliminary insight into the associations between management actions and ecological outcomes. The results show that MERLs are associated with reduced anthropogenic pressures and improved ecological conditions relative to surrounding areas, although spatial heterogeneity in outcomes persists. The proposed framework provides a structured approach for examining interactions among pressures, ecosystem states, and governance responses, and provides quantitative evidence supporting conservation effectiveness assessment at a provincial scale. The proposed framework may also support adaptive management and policy optimization for MERLs and provide practical reference for the implementation of Other Effective Area-Based Conservation Measures (OECMs).

A refined stratigraphic framework for the Tremadocian–Floian stage boundary (Lower Ordovician) in the North China Block - Xiang-Ri Chi; Guan-Zhou Yan; Mikael Calner; Fang-Yi Gong; Xiao-Cong Luan; Rong-Chang Wu (Palaeoworld, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Engineering catalytic sites in ZnIn2S4 via Mg doping: A S-to-In shift toward enhanced photocatalytic H2 evolution - Yan Wang; Yuqi Shi; Xin Chong; Chao Wang; Rong Fu; Chang Liu; Yuelan Zhang (Chemical Engineering Journal, 2026)

Bidirectional electron transfer enabled by dual electric fields for efficient 4-nitrophenol removal on a bifunctional FeCoNiP/PCN heterojunction - Yan Wang; Chang Liu; Rong Fu; Chao Wang; Xin Chong; Yuqi Shi; Yuelan Zhang (Journal of Environmental Chemical Engineering, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

One new aryltetralin lignan and other components from Blachia pentzii - Yan-Yan Zhang; Feng-Cheng Zhang; Yue Zhang; Hong-Yan Yu; Hai-Rong Xu; Xiao-Yun Dong; Chang-Shui Yang (Phytochemistry Letters, 2025)

Correction: Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Development of a Phage‐Display Derived Peptide‐Based Colloidal Gold Strip for Rapid Detection of Enterocytozoon hepatopenaei via Spore Wall Protein Interaction - Jia‐rong Xie; Hao Li; Ben Chen; Yan‐chang Fan; Yu‐hao Gong; Liqun Lu (Journal of Fish Diseases, 2025)
Infection by Enterocytozoon hepatopenaei (EHP) leads to stunted or arrested growth in shrimp, causing significant economic losses in shrimp aquaculture. In this study, the spore wall protein EhSW12 was expressed using a prokaryotic expression system. Subsequently, phage display technology was employed to screen for peptides that interact with EhSW12. A rapid detection method was developed that bypasses the laborious procedure of extracting tissue DNA samples. Instead, enzymatic digestion was used to lyse the spore wall protein present in tissue homogenates, thereby enabling direct detection of EhSW12 via antigen colloidal gold rapid test strips and dot blot assays. The colloidal gold test strips, noted for their convenience and rapidity, satisfy the requirements for on‐site testing, while the dot blot method—with its simple operation—is well suited for high‐throughput sample analysis. Both methods were compared with the national standard qPCR assay. Specificity was validated using various shrimp antigens prepared in the laboratory; the results demonstrated that only the EHP antigen yielded a positive reaction, with no cross‐reaction observed with other common shrimp pathogens (e.g., white spot syndrome virus, decapod iridescent virus and highly pathogenic Vibrio ). Sensitivity tests indicated that the minimum detection limits for the test strip and dot blot methods were, respectively, 7 × 10 6 copies and 5.2 × 10 4 copies. In summary, both methods exhibit strong specificity, high sensitivity, rapid detection speed and operational simplicity—characteristics that make them highly suitable for large‐scale on‐site rapid testing.

Neuroprotective Effects, Mechanisms of Action and Therapeutic Potential of the Kv7/KCNQ Channel Opener QO-83 in Ischemic Stroke - Huiran Zhang; Yanfei Tian; Yan Zhang; Yan Wang; Jinlong Qi; Xiangyu Wang; Yi Yuan; Rong Chen; Yupeng Zhao; Chang Liu; Najing Zhou; Lanxin Liu; et al. (Translational Stroke Research, 2025)

OsR126 IncRNA integrates AtWRKY46 and AtEM1 into ABA signaling in Arabidopsis - Lingyun Chang; Shengyi Liu; Nan Zhang; Dongxu Yang; Ziguang Liu; Hongli Yuan; Rong Yan; Xingguo Lan; Yasushi Yukawa; Juan Wu (Plant Cell Reports, 2025)

Inactivation performance of virus and bacterium in water by dielectric barrier discharge coupled with pulse corona discharge plasma - Pengcheng Yan; Rong Zhang; Min Zhang; Chang Wen; Yuxin Cheng; Zhenghui Liu; Guangzhou Qu; Ronghua Li; Tiecheng Wang; Fei Ling (Journal of Water Process Engineering, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Degradation of biodegradable plastic films in soil: microplastics formation and soil microbial community dynamics - Yue Wang; Run-Hao Bai; Qi Liu; Qiu-Xiang Tang; Chang-Hong Xie; Aurore Richel; Christophe Len; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

New data on the Cambrian–Ordovician (Tremadocian) conodont biostratigraphy of Guizhou Province, Southwest China - Hadi Jahangir; Guan-Zhou Yan; Rong-Chang Wu; Ren-Bin Zhan (Palaeoworld, 2024)

Epidemiological and genomic analysis revealed the significant role of flies in dissemination of carbapenem-resistant Enterobacteriaceae (CRE) in China - Hongwei Zhou; Hanyu Wang; Kaichao Chen; Miaomiao Xie; Zelin Yan; Yanyan Zhang; Yuchen Wu; Dejun Liu; Juan Wang; Ning Dong; Chang Cai; Yongning Wu; et al. (Journal of Hazardous Materials, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

The morphology of liquid CO2 hydrate films at different temperatures under saturation pressure - Yu-Jie Zhu; Yu Zhang; Yu-Zhou Chen; Yan Xie; Jin-Rong Zhong; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Experimental Study on Acoustic Emission Properties and Damage Characteristics of Basalt Exposed to High Temperature Treatment - Wenzhao Chen; Rong Hu; Xiqi Liu; Gang Wang; Bingwen Gong; Yan Chang; Heng Deng; Chunming Qi (Geotechnical and Geological Engineering, 2024)

Bibliometric study of the application of the chicken embryo chorioallantoic membrane model in cancer research: the top 100 most cited articles - Chang Song; Dan-Dan Xiong; Rong-Quan He; Xiang-Zhi Yong; Zhi-Guang Huang; Yi-Wu Dang; Gang Chen; Yu-Yan Pang; Chun-Yan Zhao; Ning Qu; Dan-Ming Wei (Journal of Comparative Pathology, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Strain partitioning dominated growth of strike-slip fault: Insight from the Tan-Lu fault in Eastern China - Rong Chu; Dan-Ping Yan; Liang Qiu; De-Shuang Chang; Qi Wang; Xian-Qiang Song; Chao Wang (Journal of Structural Geology, 2024)

Landfill leachate treatment by direct contact membrane distillation: Impacts of landfill age on contaminant removal performance, membrane fouling and scaling - Zhimeng Yang; Songze Lin; Linxiong Ye; Dan Qu; Haiyang Yang; Haiqing Chang; Huarong Yu; Zhongsen Yan; Hongwei Rong; Fangshu Qu (Desalination, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Cultivation mode of Saccharina japonica impacts planktonic and epiphytic microbiomes - Yongwei Yan; Shanshan Wang; Shaojun Pang; Kuimei Liu; Lirong Chang; Xiaojun Rong; Jie Li (Algal Research, 2024)

An appropriate amount of straw replaced chemical fertilizers returning reduced net greenhouse gas emissions and improved net ecological economic benefits - Lian Zhang; Guoliang Jiang; Rusheng Xiao; Kun Hou; Xin Liu; Xinyu Liu; Pei Yuan; Feng Tian; Lichu Yin; Hongmei Zhu; Chang Tian; Lan Yang; et al. (Journal of Cleaner Production, 2024)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

A 3D phytic acid cross-linked high-porous conductive hydrogel integrating g-C3N4 for electrochemical multiplex sensing of heavy metal ions - Lu Xiao; Yulan Zhao; Gang Chang; Huiling Yan; Rong Zou; Xiuhua Zhang; Shengfu Wang; Hanping He (Analytica Chimica Acta, 2023)

Heavy metal(loid)s in agriculture soils, rice, and wheat across China: Status assessment and spatiotemporal analysis - Cheng-Chen Wang; Qiao-Chu Zhang; Chang-An Yan; Guo-Yong Tang; Meng-Yan Zhang; Lena Q. Ma; Rong-Hui Gu; Ping Xiang (Science of The Total Environment, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

Conodont biostratigraphy and carbon isotope chemostratigraphy of the Middle to Upper Ordovician on the western Yangtze Platform, South China - Fang-Yi Gong; Guan-Zhou Yan; Rong-Chang Wu (Palaeoworld, 2023)

An endogenous neuropeptide hormone assists cancer cells in escaping from immune surveillance - Chang-Yu Yan; Yan-Ping Wu; Yi-Fang Li; Rong-Rong He (Science China Life Sciences, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Adsorption properties and mechanism of ginkgo biloba leaf-based materials for Cd (II) in aqueous solution - Yan-rong Cai; Yang Song; Chun Chang (Environmental Science and Pollution Research, 2022)

Antifungal and insecticidal activities of rhein derivatives: synthesis, characterization and preliminary structure–activity relationship studies - Xiang Zhu; Shunshun Chen; Yan Zheng; Yong Zhang; Tom Hsiang; Rong Huang; Jingwei Qi; Tian Gan; Yue Chang; Junkai Li (Natural Product Research, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Serum- and Feeder-Free Culture of Juvenile Monkey Female Germline Stem Cells and Testosterone Regulation of their Self-Renewal - Xiaoyong Li; Xiaoying Yao; Chunlan Mu; Zhaoxia Wang; Rong Hu; Yan Chang; Ji Wu (Stem Cell Reviews and Reports, 2022)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Evaluation of field resistance to brown stripe disease in novel and major cultivated sugarcane varieties in China - Xiao-Yan Wang; Xiao-Yan Cang; Wei Qin; Hong-Li Shan; Rong-Yue Zhang; Chang-Mi Wang; Wen-Feng Li; Ying-Kun Huang (Journal of Plant Pathology, 2021)

Phytoremediation of Cadmium Contaminated Soil: Impacts on Morphological Traits, Proline Content and Stomata Parameters of Sweet Sorghum Seedlings - Xicun Dong; Yan Chang; Rong Zheng; Xueqiang Wang; Xia Yan; Xiao-Fei Ma (Bulletin of Environmental Contamination and Toxicology, 2021)

Antidepressant Effect of Paeoniflorin Is Through Inhibiting Pyroptosis CASP-11/GSDMD Pathway - Dan-Dan Tian; Min Wang; An Liu; Mei-Rong Gao; Chen Qiu; Wen Yu; Wen-Ju Wang; Kun Zhang; Le Yang; Yan-Yan Jia; Chang-Bin Yang; Yu-Mei Wu (Molecular Neurobiology, 2021)

Heavy metal concentrations and associated health risks in edible tissues of marine nekton from the outer Pearl River Estuary, South China Sea - Chang-Ping Yang; Yan Liu; Bin-Bin Shan; Jing Xu; Wei Yu; Dian-Rong Sun; Zai-Wang Zhang (Environmental Science and Pollution Research, 2021)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

Hyperinsulinemia-induced KLF5 mediates endothelial angiogenic dysfunction in diabetic endothelial cells - Xi-hui Wang; Chang-you Yan; Jian-rong Liu (Journal of Molecular Histology, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Polybrominated diphenyl ethers in cord blood and perinatal outcomes from Laizhou Wan Birth Cohort, China - Limei Chen; Caifeng Wang; Yan Zhang; Yijun Zhou; Rong Shi; Chang Cui; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2018)

Protective effect of the total flavonoids from Apocynum venetum L. on carbon tetrachloride-induced hepatotoxicity in vitro and in vivo - Wei Zhang; Zheng Dong; Xiujuan Chang; Cuihong Zhang; Guanghua Rong; Xudong Gao; Zhen Zeng; Chunping Wang; Yan Chen; Yihui Rong; Jianhui Qu; Ze Liu; et al. (Journal of Physiology and Biochemistry, 2018)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

Tree architecture varies with forest succession in evergreen broad-leaved forests in Eastern China - Xiao-Dong Yang; En-Rong Yan; Scott X. Chang; Liang-Jun Da; Xi-Hua Wang (Trees, 2015)

Regulatory effect of AMP-activated protein kinase on pulmonary hypertension induced by chronic hypoxia in rats: in vivo and in vitro studies - Xiaoying Huang; Rong Fan; Yuanyuan Lu; Chang Yu; Xiaomei Xu; Xie Zhang; Panpan Liu; Shuangquan Yan; Chun Chen; Liangxing Wang (Molecular Biology Reports, 2014)

Soil nitrification and foliar δ15N declined with stand age in trembling aspen and jack pine forests in northern Alberta, Canada - Ya-Lin Hu; En-Rong Yan; Woo-Jung Choi; Francis Salifu; Xiao Tan; Z. Chi Chen; De-Hui Zeng; Scott X. Chang (Plant and Soil, 2014)

Genetic engineering techniques for lactic acid bacteria: construction of a stable shuttle vector and expression vector for β-glucuronidase - Shiao-Ming Chang; Tsong-Rong Yan (Biotechnology Letters, 2014)

Effect of Hyperoxia on the Viability and Proliferation of the Primary Type II Alveolar Epithelial Cells - Xiu-xiang Liu; Xiu-rong Yu; Xiu-hong Jia; Ke-xuan Wang; Zheng-yan Yu; Chang-jun Lv (Cell Biochemistry and Biophysics, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Effectiveness of soil N availability indices in predicting site productivity in the oil sands region of Alberta - En-Rong Yan; Ya-Lin Hu; Francis Salifu; Xiao Tan; Z. Chi Chen; Scott X. Chang (Plant and Soil, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Imprinting analysis of porcine MAGEL2 gene in two fetal stages and association analysis with carcass traits - Ling Guo; Mu Qiao; Chao Wang; Rong Zheng; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2012)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Molecular characterization and expression patterns of Lbx1 in porcine skeletal muscle - Zhe Chao; Jian Wu; Rong Zheng; Feng-E. Li; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2011)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

DNA sequence analysis of a cryptic plasmid pL2 from Lactococcus lactis subsp. lactis - Shiao-Ming Chang; Tsong-Rong Yan (Biotechnology Letters, 2007)

Effects of predator-mediated apparent competition on the population dynamics of Tetranychus urticae on apples - Chang-zhong Liu; Lin Yan; Hua-rong Li; Gang Wang (BioControl, 2006)

Detection of the organophosphorus nerve agent sarin by a competitive inhibition enzyme immunoassay - Yong-xin Zhou; Qing-jin Yan; Yun-xiang Ci; Zhen-quan Guo; Kang -Tai Rong; Wen-bao Chang; Yu-fen Zhao (Archives of Toxicology, 1995)